TINGKAT KONSUMSI IKAN DAN PRESTASI BELAJAR ANAK DI SDN 8 PADANG SAMBIAN KAJA DENPASAR - Anggita Paulina ina Munde; I Made Suarjana; I Putu Suiraoka (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
Fish is a food source of animal protein. Fish contain unsaturated fatty acids in the form of omega-3, EPA, and DHA which can improve children's intelligence and improve academic abilities. Learning achievement is the mastery of knowledge and skills that are developed in subjects, usually indicated by the value of the test given by the teacher. The purpose of this study was to find out the relationship between the level of consumption of fish and learning achievement at SDN 8 Padang Sambian Kaja, Denpasar. This study uses observational methods with a cross sectional design. The independent variable in this study was the level of fish consumption and the dependent variable learning achievement. The instrument used was sample identity, the SQ-FFQ fish consumption questionnaire. The sample in this study were grade IV and V students of SDN 8 Padang Sambian Kaja with a total of 70 samples. The data obtained were analyzed using Chi-square test. Based on the results of the Chi-square test the relationship between fish consumption and learning achievement obtained significant results, namely p = 0.37 or (p 0.05), the meaning proved to be no relationship between fish consumption and learning achievement.